2011
DOI: 10.1016/j.jmb.2011.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Probing Dimerization and Structural Flexibility of Mammalian Lipoxygenases by Small-Angle X-ray Scattering

Abstract: Human lipoxygenases (LOXs) and their metabolites have a great impact on human homeostasis and are of interest for targeted drug design. This goal requires detailed knowledge of their structures and an understanding of structure-function relationship. At the moment, there are two complete crystal structures for mammalian LOX [rabbit 12/15LOX (r-12/15LOX) and human 5LOX (h-5LOX)] and a fragment of human 12LOX. The low-resolution structures in solution for various LOX isoforms have brought about controversial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 38 publications
(63 reference statements)
1
46
1
2
Order By: Relevance
“…3o8y shows a crystallographic dimer, which is not a thermodynamically stable complex (Shang et al , 2011 ). Therefore, this assembly might solely rise from crystal-packing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…3o8y shows a crystallographic dimer, which is not a thermodynamically stable complex (Shang et al , 2011 ). Therefore, this assembly might solely rise from crystal-packing.…”
Section: Discussionmentioning
confidence: 97%
“…In most reviews, 5-LO is mentioned as a monomeric enzyme (Rouzer and Samuelsson , 1985 ;R å dmark, 2002 ), nevertheless, it was previously shown that 5-LO from rat basophilic leukemia cells (RBL-1) forms dimers in the presence of calcium (Parker and Aykent , 1982 ). Recently, Shang et al analyzed dimerization and fl exibility of rabbit 12/15-LO and human 12-LO by small angle X-ray scattering (SAXS) (Shang et al , 2011 ). The outcome of their study was that (i) r12/15-LO is mainly monomeric, but dimerizes at higher protein concentrations and with increasing protein fl exibility, and (ii) that human 12-LO is stable as a dimer confi rming their former studies for 12-LO (Aleem et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A number of spectroscopic studies, such as small angle X-ray scattering [116,117], dynamic fluorescence studies and fluorescence resonance energy transfer measurements [44,118], as well as various computational methods [117,119] have been applied to explore the motional flexibility of rabALOX15 in aqueous solutions. Summarizing these results one may conclude that three elements contribute to structural flexibility: (1) Ligand binding induces conformational alterations: Binding of an inhibitor (R7) at the active site induces conformational alterations and helices α2-and α18 are particularly affected [112].…”
Section: Solution Structurementioning
confidence: 99%
“…As curvas p(r) experimentais foram obtidas usando o programa GNOM. Os ajustes mostrados junto com a p(r) experimental foram realizados com a combinação linear das curvas de p(r) teóricas obtidas para a estrutura cristalográfica da HbLt, mostradas na Figura Vários estudos, baseados na técnica de SAXS, são reportados na literatura para os processos de dissociação, desnaturação e agregação para diferentes proteínas, induzidos por variação de pH, altas concentrações de sal e presença de cloreto de guanidina [44,45,49,[61][62][63][64][65][66].…”
Section: Fonte-unclassified
“…Nesses estudos a caracterização de espécies dissociadas em solução também é descrita, principalmente para sistemas envolvendo o equilíbrio de homo-dimeros com os monômeros correspondentes [62,64]. Além disso, existem também estudos para proteínas oligoméricas, tais como, homo-tetrâmero e homo-hexâmero [58,66].…”
Section: Fonte-unclassified